West Africa spatial analysis prototype exploratory analysis: The effect of ssettlement zones and economic diversity on reproductive behavior in West Africa - Saha, Tulshi (DHS Spatial Analysis Reports No. 3, 1998)
The goal of this study is to measure the relationship between reproductive behavior and settlement zones and economic diversity in twelve countries (Benin, Burkina Faso, Cameroon, Central African Republic, Cote d'Ivoire, Ghana, Liberia, Mali, Niger, Nigeria, Senegal, and Togo). The purpose of this study is to testis to test the proposition that settlement zone, as measured by the rate of urbanization and the extent to which town and rural areas have become integrated, and economic diversity, as measured by the number of different economic sectors operating in each administrative unit, affect reproductive behaviors, such as knowledge of family planning, use of family planning methods, and the demand for family planning.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The Demographic and Health Surveys (DHS) is a 13-year project to assist government and private agencies in developing countries to conduct national sample surveys on population and maternal and child health. Funded primarily by the United States Agency for International Development (USAID), DHS is administered by Macro International Inc. in Columbia, Maryland, USA.